1998
DOI: 10.1056/nejm199804303381803
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Defects and Clinical Characteristics of Patients with a Form of Oculocutaneous Albinism (Hermansky–Pudlak Syndrome)

Abstract: The 16-bp duplication in exon 15 of HPS, which we found only in Puerto Rican patients, is associated with a broad range of pigmentation and an increased risk of restrictive lung disease in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
306
1
5

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 276 publications
(318 citation statements)
references
References 24 publications
(20 reference statements)
1
306
1
5
Order By: Relevance
“…2 4 Little is known of the genetic basis or likely long term prognosis of this disease for non-Puerto Rican patients; although limited reports suggest that pulmonary complications are particularly associated with HPS-1 mutations in Puerto Rican patients and are not found in other patients. 15 In this study we report for the first time clustering of HPS in families originating from Turkey, especially the Turkish/ Kurdish border, and from Pakistan. Twelve children in this series were members of four Turkish kindreds in which there was intermarriage and consanguinity.…”
Section: Discussionmentioning
confidence: 66%
“…2 4 Little is known of the genetic basis or likely long term prognosis of this disease for non-Puerto Rican patients; although limited reports suggest that pulmonary complications are particularly associated with HPS-1 mutations in Puerto Rican patients and are not found in other patients. 15 In this study we report for the first time clustering of HPS in families originating from Turkey, especially the Turkish/ Kurdish border, and from Pakistan. Twelve children in this series were members of four Turkish kindreds in which there was intermarriage and consanguinity.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, these results suggested that patients 88 and 156 suffer from HPS due to mutations causing BLOC-2 deficiency, and that patients 45, 94 and 128 suffer from HPS due to BLOC-3 deficiency. Based on reported differences in the severity of HPS disease caused by BLOC-2 deficiency (in HPS-3, -5 or -6 [8,11,[29][30][31][32]) or BLOC-3 deficiency (in HPS-1 or -4 [18][19][20][21][22][23]), one would then expect that patients 88 and 156 should suffer from a mild form of HPS and that patients 45, 94 and 128 should be at a higher risk of developing pulmonary fibrosis or GI disease. Unfortunately, only two of these patients (88 and 45) were examined at an age in which the validity of these predictions could begin to be evaluated: at the time of their last evaluation at the NIH Clinical Center, patients 88 (age 40 years), 94 (age 2 years), 128 (age 2 years) and 156 (age 19 years) had no signs of interstitial lung disease of GI disease, while patient 45 (age 35 years) presented with a history of GI disease but no interstitial lung disease.…”
Section: Analysis Of Samples From Hps Patients Of Unknown Genetic Lesmentioning
confidence: 99%
“…Clinical characterization of some HPS types has begun to lend support to this notion. Thus, both HPS-1 and -4, and not other HPS types, are associated with increased risks of developing pulmonary fibrosis (which can be fatal) and gastro-intestinal (GI) manifestations such as granulomatous colitis [18][19][20][21][22][23], although that may not be the case for HPS-1 patients from a Swiss isolate [3]. HPS-2, and not the other HPS types, is associated with recurrent infections due to chronic neutropenia and other deficiencies in the innate immune system [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The triad is oculocutaneous albinism, bleeding tendency, and ceroid accumulation in lysosomes of macrophages (1,2) and is considered to be due to a deficiency of lysosome-related organelles; such as melanosomes, platelet dense bodies, and so on (3-6). Patients will be diagnosed as having HPS based upon a paucity or deficiency of platelet dense bodies on whole mount electron microscopy or confirming ceroid accumulation under a microscope.…”
Section: Discussionmentioning
confidence: 99%